The 2020/2021 Tokyo Olympics: Does Japan get the gold medal or the wooden spoon?. Issue 1 (2nd January 2023) - O'Shea, Paul; Maslow, Sebastian
ABSTRACT: The Tokyo 2020/2021 Olympics will go down in history as the 'Pandemic Games'. Postponed by a year due to Covid-19, they were eventually held despite broad public protest and amidst the Delta variant wave. Japan brought home a record haul of medals, yet Prime Minister Suga Yoshihide resigned in ignominy shortly after the Games ended. So, was Tokyo 2020/2021 a 'success' or a 'failure', and for whom? We examine the policy and politics of the Games, considering the attribution of 'success' and 'failure' to the Olympics across a range of issues, actors, and narratives. Reviewing their economic, public health, soft power, and political impact, we find that the Tokyo 2020/2021 Olympics remain deeply ambiguous. Prime Minister Abe Shinzō's vision of a proud, 'reborn' Japan showcasing itself to the world obviously did not come to pass; neither did the promise of a 'Recovery Olympics' aiding in the reconstruction of the post-3/11 Tohoku region. Conversely, the predictions of a COVID-19 catastrophe, of even an 'Olympic variant', also failed to transpire. Rather, the Olympics became a pared-down event forced through by vested interests, notably the IOC and Dentsu. The political fallout was contained by one-party dominance in Japan's democracy, where even a forced mega-event during a pandemic was insufficient to threaten the Liberal Democratic Party's stranglehold on power.